Potential Problems with Peer Ratings - DeNisi, Angelo S.; Randolph, W. Alan; Blencoe, Allyn G. (Academy of Management Journal, 1983)
A study of the reactions of workers to evaluations by their peers found that negative peer rating feedback produced significantly lower perceived performance, cohesiveness, satisfaction, and peer ratings on a subsequent task. Positive peer rating feedback produced higher but nonsignificant values for these variables on a subsequent task.